2014
DOI: 10.1039/c4tb01155d
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated reversible shape switch of polymer particles

Abstract: Shape-switchable micrometer-sized particles have the ability to reversibly switch their shapes between 43 and 0 °C via a two-way shape memory effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 57 publications
(66 reference statements)
2
71
0
Order By: Relevance
“…In multiphase co‐polyester urethane networks capable of a rSME, poly( ε ‐caprolactone) segments are responsible for actuation and poly( ω ‐pentadecalactone) forms the skeleton . Polymer networks prepared from six‐armed poly(ethylene glycol)‐poly( ε ‐caprolactone) precursors have been applied to fabricate particles that can reversibly change their shape upon cyclic heating and cooling . Ellipsoidal temporary shaped particles were obtained by embedding the spherical particles in a modified polyvinyl alcohol film and stretching of the film at 60°C and subsequent fixation at 0°C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In multiphase co‐polyester urethane networks capable of a rSME, poly( ε ‐caprolactone) segments are responsible for actuation and poly( ω ‐pentadecalactone) forms the skeleton . Polymer networks prepared from six‐armed poly(ethylene glycol)‐poly( ε ‐caprolactone) precursors have been applied to fabricate particles that can reversibly change their shape upon cyclic heating and cooling . Ellipsoidal temporary shaped particles were obtained by embedding the spherical particles in a modified polyvinyl alcohol film and stretching of the film at 60°C and subsequent fixation at 0°C .…”
Section: Introductionmentioning
confidence: 99%
“…Polymer networks prepared from six‐armed poly(ethylene glycol)‐poly( ε ‐caprolactone) precursors have been applied to fabricate particles that can reversibly change their shape upon cyclic heating and cooling . Ellipsoidal temporary shaped particles were obtained by embedding the spherical particles in a modified polyvinyl alcohol film and stretching of the film at 60°C and subsequent fixation at 0°C . Free‐standing rSME have been reported for covalently crosslinked poly[ethylene‐ co ‐(vinyl acetate)] (cPEVA) as well as for a copolymer network, named cPCLBA, containing crystallizable PCL and amorphous poly( n ‐butylacrylate) segments .…”
Section: Introductionmentioning
confidence: 99%
“…In this study the authors suggested that it would be possible to either promote or deter phagocytosis in future studies employing iterations of these particles. [31] Temperature-responsive composites-based on polycaprolactone and poly(sebacic anhydride), have been shown to be capable of delivering paracetamol (5 wt% loading) by passive diffusion while maintaining their SMP properties, [32] and ultrasound-responsive SMP-based drug delivery devices have been developed for the delivery of copper sulfate (formerly used as an emetic and antimalarial), [31] or a high molecular weight model drug (lysozyme), [33] which may find application in the emerging area of ultrasound-mediated drug delivery systems. [34] Lendlein and co-workers have made some interesting contributions to the literature with temperature-responsive degradable caprolactone-based polymers for the delivery of hydrophilic drugs (such as ethacridine lactate) and hydrophobic drugs (e.g., enoxacin).…”
Section: Smp-based Materials With Speculative Application As Drug Delmentioning
confidence: 97%
“…(c)] reversible shape memory (RSM) transformations . This new class of materials significantly extends the range of practical applications for programmable shape‐shifting …”
Section: Introductionmentioning
confidence: 99%